Corporeidade e performatividade: relações e fricções (2018)
The notions of corporeality and performativity occupy a place of importance in contemporary research of theater, dance and performance art. Still, little is investigated on the relation between them, which makes their differences and their similarities not as widely discussed in the field of the arts of the body as it could. Due to the inherent complexity of both corporeality notion as the notion performativity, this article does not aim to exhaust the discussions which emerge when such notions are placed in relation and rubbed. It is intended here to present some indications that allow a connection between those notions, under the perspective of Mapas e Hipertextos’ creation process, a research and creation art collective headquartered in Florianopolis, Brazil.